Pembelajaran berbasis project pada kurikulum merdeka di SD BPPI Cokcroaminoto Pare - Kunaenih Kunaenih; Mugiyono Mugiyono; Nadia Izzatul Jannah; Kemal Thorieq; Nizar Alfarisi (SAP (Susunan Artikel Pendidikan), 2025)
The purpose of this study is to analyze project-based learning in the Merdeka Curriculum at SD BPPI Cokroaminoto. Using a qualitative approach, data was collected through observation, in-depth interviews, and documentation. The findings indicate that project-based learning is implemented through several stages, including material introduction, activity design, and project execution. Students demonstrated a high level of enthusiasm, especially for projects that allowed them to apply knowledge practically. However, the main challenge faced is the diversity of students' interests and abilities, requiring teachers to adapt methods and provide flexibility for students in developing their projects. Interviews with students and teachers revealed that students are actively engaged in observing, exploring, and solving real-world problems through project-based learning. This process not only fosters critical thinking and creativity but also enhances student participation in learning. Despite some challenges, the implementation of project-based learning within the Merdeka Curriculum is expected to address existing issues and enrich students' learning experiences.